Advances in the study of selenium and human intestinal bacteria - Cai, Jinzhong; Su, Weizhu; Chen, Xianxian; Zheng, Heng (Frontiers in Nutrition, 2022)
Selenium is an essential trace element for human health and has received great attention due to its contribution to health. Currently, attention is being paid to the regulatory mechanisms of selenium on human health, especially the regulatory mechanisms of selenium on human intestinal flora and its effects on diseases. This review deals with the effects of selenium on human health, the relationship between selenium and human gut microbiota, and the progress of research between selenium, gut flora and diseases. In addition, the current state of research on the selenium-human gut flora-disease interface is also presented.